Pendampingan Komersialisasi Tanaman Obat Keluarga (TOGa) melalui Penggunaan Media Sosial dan Pencatatan Keuangan Digital untuk Menunjang Pendapatan Warga Desa Karangrejo, Kecamatan Kawedanan, Kabupaten Magetan - Yudha Adi Kusuma; Alim Citra Aria Bima (Universitas Muhammadiyah Manado, 2023)
Commercial activities contribute to increasing sales of agricultural products. One of the agricultural products is Tanaman Obat Keluarga (TOGa). TOGa plants are an additional source of income. However, the difficulty of selling is that often the price is not as good as the market. Through assistance in the use of social media and digital financial records, it is expected to contribute to increasing the income of residents of Purwoseco Hamlet and Karangrejo Hamlet. The results of service activities show that > 50% of residents experience an increase in understanding and knowledge of the knowledge provided. The satisfaction level of service participants showed an average score of 65%, which is very good. This shows that the service participants are satisfied with the course of service activities.